The Big Difference a Small Island Can Make: How Jamaican Adolescents Are Advancing Acculturation Science. (28th October 2013) - Ferguson, Gail M.
Abstract: New research with Jamaican adolescents has brought acculturation science into closer accord with two 21st‐century cultural realities: (a) multicultural destination societies for immigrant families and (b) intercultural contact among nonimmigrant families via modern globalization mechanisms. In this article, I review two theoretical expansions to the traditional conceptualization of acculturation (i.e., tridimensional acculturation and remote acculturation) along with supporting empirical evidence among Jamaican adolescents in the United States and on the Caribbean island. First, bidimensional acculturation lenses are exchanged for tridimensional ones to capture the acculturation of immigrant youth for whom three cultural dimensions are relevant. Second, acculturation pathways are expanded to include modern indirect and/or intermittent intercultural contact for nonimmigrant youth. Tridimensional and remote acculturation may be modern mechanisms by which today's and tomorrow's adolescents produce their own development. These advances reveal new avenues to investigate adolescent acculturation and adaptation in their increasingly complex cultural neighborhoods.